2016
DOI: 10.1002/ange.201607793
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Pentelidene Complexes with Diazoalkanes: Stabilization of Parent 2,3‐Dipnictabutadienes

Abstract: The reaction of the phosphinidene complex [Cp*P{W(CO) 5 } 2 ]( 1a)w ith diphenyldiazomethane leads to [{W(CO) 5 }Cp*P=NN{W(CO) 5 }=CPh 2 ]( 2). Compound 2 is ar are example of ap hosphadiazadiene ligand (R-P = N À N = CR'R'')c omplex. At temperatures above08 8C, 2 decomposes into the complex [{W(CO) 5 }PCp*{N(H)N = CPh 2 ) 2 ]( 3), among other species.The reaction of the pentelidene complexes [Cp*E{W(CO) 5 } 2 ]( E= P, As) with diazomethane (CH 2 NN) proceeds differently.For the arsinidene complex (1b), only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…60 o with respect to the Mo2PN plane, thus completing a distorted trigonal bipyramidal (TBP) environment around the P atom, as found in the mentioned derivatives of 1. This local geometry around phosphorus has been also found in different derivatives of the trigonal phosphinidene complex [Mo2Cp{- 1 : 1 , 5 -PC5H4}( 6 -HMes*)(CO)2] with carbene, 7 chalcogens, 14 alkynes, 15 and metal carbonyl fragments 16 added at the MoP multiple bond of this substrate, although in these cases steric effects seem to play a significant role too. We further note that the P atom in compounds 2b and 3 bridges the Mo atoms in a symmetrical way (MoP lengths ca.…”
Section: Scheme 5 Diazoalkane Derivatives Of 1 Asupporting
confidence: 53%
See 1 more Smart Citation
“…60 o with respect to the Mo2PN plane, thus completing a distorted trigonal bipyramidal (TBP) environment around the P atom, as found in the mentioned derivatives of 1. This local geometry around phosphorus has been also found in different derivatives of the trigonal phosphinidene complex [Mo2Cp{- 1 : 1 , 5 -PC5H4}( 6 -HMes*)(CO)2] with carbene, 7 chalcogens, 14 alkynes, 15 and metal carbonyl fragments 16 added at the MoP multiple bond of this substrate, although in these cases steric effects seem to play a significant role too. We further note that the P atom in compounds 2b and 3 bridges the Mo atoms in a symmetrical way (MoP lengths ca.…”
Section: Scheme 5 Diazoalkane Derivatives Of 1 Asupporting
confidence: 53%
“…Scheer et al also found that reactions of [W2(-PCp*)(CO)10] with diazoalkanes can lead to phosphadiazadiene-or phosphaalkene-bridged derivatives, depending on the particular reagent used (N2CPh2 vs. N2CH2), although additional products were observed in the reaction with diazomethane. 5 In contrast, reaction of this ditungsten complex with azides N3R (R = Hex, Cy) proceeded selectively without denitrogention to yield triazaphosphete-bridged complexes (Scheme 2), which model the intermediate species proposed for the Staudinger reaction. 6 Scheme 2.…”
Section: Scheme 1 Azide and Diazoalkane Derivatives Of Pr-complexes Of Type A Amentioning
confidence: 99%